The Utilization level of Corn Cob Fermented by MOIYL on Dry Matter and Organic Matter Digestibility on Local Rabbit - Noviani Noviani; Yunilas Yunilas; Ma'ruf Tafsin (Universitas Sumatera Utara, 2018)
The study aims to evaluated the value of dry matter and organic matter digestibility of feed containing corn cob fermented by MOIYL on local rabbit. Research conducted at Desa Bandar Klippa Deli Serdang, North Sumatera Province, in January – March 2018. The study used 20 local rabbit with initial weight 404,4 gram ± 9,14 and design experiment used completely randomized design (CDR), which consists of 4 treatments and five replications. The treatment consisted of ration P0= unfermented ,P1=10%, P2= 20, and P3= 30%. Variable measured were consumption of dry matter and organic matter, digestibility of dry matter and organic matter. The Results showed that fermented of corn cob with probiotics MOIYL provide a significant effect (P<0,01) increasing corn cob fermented by MOIYL to the level 30% increase dry matter and organic matter digestibility. The conclusion of this study is corn cob fermantation by probiotics MOIYL till the level 30% can increase the digestibility of dry matter and organic matter on local rabbit.